A genomic island integrated into recA of Vibrio cholerae contains a divergent recA and provides multi‐pathway protection from DNA damage. (26th June 2014) - Rapa, Rita A.; Islam, Atiqul; Monahan, Leigh G.; Mutreja, Ankur; Thomson, Nicholas; Charles, Ian G.; Stokes, Harold W.; Labbate, Maurizio
Summary Lateral gene transfer (LGT) has been crucial in the evolution of the cholera pathogen, Vibrio cholerae. The two major virulence factors are present on two different mobile genetic elements, a bacteriophage containing the cholera toxin genes and a genomic island (GI) containing the intestinal adhesin genes. Non‐toxigenic V. cholerae in the aquatic environment are a major source of novel DNA that allows the pathogen to morph via LGT. In this study, we report a novel GI from a non‐toxigenic V. cholerae strain containing multiple genes involved in DNA repair including the recombination repair gene recA that is 23% divergent from the indigenous recA and genes involved in the translesion synthesis pathway. This is the first report of a GI containing the critical gene recA and the first report of a GI that targets insertion into a specific site within recA. We show that possession of the island in Escherichia coli is protective against DNA damage induced by UV‐irradiation and DNA targeting antibiotics. This study highlights the importance of genetic elements such as GIs in the evolution of V. cholerae and emphasizes the importance of environmental strains as a source of novel DNA that can influence the pathogenicity of toxigenic strains.